Age, length-weight relationships and condition factors of endemic Antalya barb Capoeta antalyensis (Battalgil, 1943) - Soner Çetinkaya; Rahmi Uysal; Vedat Yegen; Mustafa Ceylan; Ufuk Akçimen; Fuat Bilgin (Journal of Fisheries, 2020)
The aim of this study was to determine the length-weight, length-length relationships (LWR and LLR) and condition factors of Antalya barb Capoeta antalyensis, an endemic species to Turkey. The specimens (N = 125) were caught using the gill nets in the Sorgun Dam (Aksu, Isparta). The age of the study specimens varied between one and six years. The total length and body weight of the specimens varied from 17.7 – 36.7 cm and 57.03 – 526.91 g respectively. A negative allometric growth (b = 2.7743) was recorded for the species whereas the LWR and total length (TL) – fork length (FL) equations were W = 0.0203 × TL2.7743 (R2 = 0.95) and TL = 0.402 + FL × 1.061 (R2 = 0.99) respectively. The condition factor was determined for every specimen. In light of the results obtained in the study this species may be considered for aquaculture ensuring sustainable population in the wild. This study provides new information that can play an important role in the sustainable management this species.